The impact of shear rate and reverse flow on cardiac morphogenesis and gene expression in the embryonic zebrafish heart - Zeller, Molly J., author; Garrity, Deborah M., advisor; Mykles, Donald, committee member; Bedinger, Patricia, committee member; Dasi, Lakshmi Prasad, committee member (Colorado State University. Libraries, 2015)
Missteps in formation of the embryonic heart can have drastic consequences, making cardiac malformations a common human birth defect. During development, biomechanical factors including shear stress and reverse flow impact cardiogenesis. Shear stress is an epigenetic biomechanical force acting upon endothelial cells. Normally, a short period of reverse flow occurs prior to atrioventricular valve formation during ventricle systole and atrial diastole. The goal of our research is to investigate how altered biomechanical forces acting on endocardial cells lead to genetic responses by the heart. The mammalian zinc finger transcription factor Krüppel-like factor 2 (KLF2) responds to shear stress signals. Here, we explore the zebrafish KLF genes: klf2a, klf2b, and klf4. Whole embryo RT-PCR indicates that the three genes are expressed throughout early development, with cardiac expression in all genes present by 48 hours post fertilization. To evaluate how changes in biomechanical environments trigger altered gene expression in endocardial cells, we used comparative qPCR to quantify klf2a, klf2b, and klf4 expression levels in embryonic hearts with altered shear stress or reverse flow. Knockdown of the hematopoiesis gene gata2 was found to decrease blood viscosity, thereby decreasing both shear stress and reverse flow. Knockdown of contractility gene filaminCb was found to decrease shear stress but significantly increase reverse flow. Using high-speed imaging we quantified these forces and correlated changes in klf2a, klf2b, and klf4 expression. klf2a expression levels decreased in response to changes in both blood viscosity and cardiac contractility. klf2b and klf4 expression levels did not significantly change with these changes in biomechanical stresses. Our investigations considered the impact of blood viscosity versus cardiac contractility on KLF expression and determined that klf2a is a flow response gene. This data confirms previous studies that klf2a is in fact a flow response gene and shows that klf2b and klf4 are not responsive to changes in blood viscosity or cardiac contractility. Future studies will use transcriptomic approaches to identify genes regulated by the KLF family in response to shear stress and reverse flow cues.
Keywords: cardiac morphology; klf; reverse flow; shear stress; zebrafish